Tourism Potential Evaluation and Strategy Formulation for Pine Forest of Gelagahlinggah; Experience From A Community Engagement - Suasapha, Anom Hery; Mertha, I Wayan; Widana, Ida Bagus Gede Agung; Wiarti, Luh Yusni; Agustini, Ni Putu Oka; Zuraida, Lukia; Putri, Diah Cynthia (E-Journal of Tourism; Volume 9 Number 1 (March 2022)DO - 10.24922/eot.v9i1.82250, 2022)
This article is written based on a research conducted as part of a series of community engagement done by Lecturers of Tourism Destination Program of Bali Tourism Polytechnic for the community of Gelagahlinggah Customary Village. The village is located at Kintamani of Bangli Regency, and is part of buffer zone for Batur UNESCO Global Geopark. The aim of the research was to evaluate the tourism potential of the pines forest of Gelagahlinggah, and to produce strategies to develop those potentials. The research implemented quantitative and qualitative approach, utilizing survey as the method for collecting primary data. To increase the validity of the data, the sample was determined purposively. Therefore, the respondents should understand the existing condition of the pines forest of Gelagahlinggah Village, and able to evaluate its tourism potentials. The questionnaire was developed on Google form to allows for practicality. A sample of 100 respondents were collected, based on which a dataset was then prepared for analysis. The analysis using Exploratory Factor Analysis (EFA) to extract factors in the form of strengths, weaknesses, opportunities and threats indicating the tourism potentials of the pine forest of Gelagahlinggah. The tourism potentials were then processed in a SWOT Matrix to develop strategies for those tourism potentials. The research result reveals some tourism potentials of the pine forest of Gelagahlinggah, and strategies suitable to develop those potentials. Keywords: tourism potentials, evaluation, pine forest, strategy